Investigation of Natural Lake Pigments Prepared With a Mixture of Hemp (Datisca cannabina L.) and Weld (Reseda luteola L.) - (:unkn) unknown (YARMOUK UNIV, DEANSHIP RESEARCH & GRADUATE STUDIES, 2018)
In this study, lake pigments (natural pigments) were prepared by adding KAl(SO4)(2)center dot 12H(2)O (alum), FeSO4 center dot 7H(2)O and SnCl2 center dot 2H(2)O solutions to hemp (Datisca cannabina L.) and weld (Reseda luteola L.) dye plant extracts. Reversed -phase high-performance liquid chromatography (RP-HPLC) with diode array detection (DAD) technique was utilized for the identification of natural dyes in the lake pigments. The dyes extraction from the lake pigments was carried out with a 37 % HCl/MeOH/H2O (2:1:1; v/v/v) mixture. The performed method was able to analyze and detect natural dyes, such as luteolin (5,7,3', 4' -tetrahydroxyflavone), apigenin (5,7,4'-trihydroxyflavone), datiscetin (3,5,7,2'-tetrahydroxyflavone), chrysoeriol (5,7,3'-OMe, 4'-flavone or 3'-methoxy derivative of luteolin), luteolin-7-O-glucoside and luteolin-3', 7-di-O-glucoside present in the lake pigments and /or the plant extracts.
Keywords: Datisca cannabina L; HPLC; Lake pigments; Natural dyes; Colour; Reseda luteola L.; PERFORMANCE LIQUID-CHROMATOGRAPHY; DACTYLOPIUS-COCCUS COSTA; POST-BYZANTINE ICONS; HPLC-DAD; IDENTIFICATION; DYES; TEXTILES; PLANTS; FLAVONOIDS; DYESTUFFS